From Light to Byte : Toward an Ethics of Digital Cinema - Hadjioannou, Markos (Book collections on Project MUSE., 2012)
Cinema has been undergoing a profound technological shift: celluloid film is being replaced by digital media in the production, distribution, and reception of moving images. Concerned with the debate surrounding digital cinema's ontology and the interrelationship between cinema cultures, From Light to Byte investigates the very idea of change as it is expressed in the current technological transition. Markos Hadjioannou asks what is different in the way digital movies depict the world and engage with the individual and how we might best address the issue of technological shift w.